Explaining gender differences in preference for self-employment among tertiary graduates in Ghana - Kehinde Ajayi; Nana Akua Anyidoho (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We examine gender differences in ambitions and expectations of jobseekers concerning self-employment, an increasingly proposed option for youth in economies with limited wage employment. Analysing survey data on 2,036 tertiary graduates in Ghana, we find that males have a stronger preference for self-employment. This is mostly explained by differences in educational background and work experience, and less by financial assets and family background. Personal traits (such as self-esteem or 'grit') do not explain gender differences. Our findings suggest early interventions may reduce gender differences in labour market outcomes, specifically by strengthening women's academic training and encouraging more pre-graduate work experience.
Keywords: I21; J16; J21; J24; O15; 330; gender; Ghana; graduate employability; higher education; self-employment